Significant changes in resting metabolic rate over a competitive match week are accompanied by an absence of nutritional periodization in male professional soccer players - Carter, J. L.; Lee, D. J.; Perrin, C. G.; Ranchordas, M. K.; Cole, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Resting metabolic rate (RMR) is an important component of total daily energy expenditure; however, it is currently not understood how it varies across a typical competitive match week in professional soccer players. For the first time, we aimed to assess RMR throughout an in-season competitive week in professional soccer players. Additionally, we aimed to assess energy and carbohydrate intake across the same week. Twenty-four professional soccer players from an English Premier League club (age: 18 ± 1.6 years) completed the study. RMR was assessed each morning of a typical competitive match week (match day [MD] -3, -2, -1, +1, +2, and + 3), and dietary intake (including MD) was assessed daily via the remote food photography method and 24-hr recall. Daily training load was quantified using Global Positioning System, daily muscle soreness ratings were recorded, and body composition was assessed via dual-energy X-ray absorptiometry. There was a significant (p = .0004) increase in mean RMR of ~261 kcal/day on MD + 1, compared with MD - 1. Additionally, volume of oxygen consumed significantly increased at MD + 1 (p = .0002) versus MD - 1. There were no significant differences in daily energy or carbohydrate intake across the competitive week (p > .05), with inadequate carbohydrate intakes on MD - 1 (~3.9 g/kg body mass), MD (~4.2 g/kg body mass), and MD + 1 (~3.6 g/kg body mass) in relation to current recommendations. We report, for the first time, that RMR is significantly increased following a competitive match in professional soccer players. In addition, we confirm previous findings to reinforce that players exhibit inadequate nutrition periodization practices, which may impair physical performance and recovery.